Hubungan Karakteristik Petani Terhadap Persepsi Dalam Pemilihan Komoditi Kentang di Kecamatan Bebesen Kabupaten Aceh Tengah - Hidayat, Erwin; Mardhiah, Ainal; Khumaira, Khumaira (Center for Research and Community Service (LPPM) University of Abulyatama, 2025)
Bebesen District is an area that has been working on potato commodities as the main vegetable farming. Potato plants in the region are known to have the advantage of relative resistance to disease. The determination of the type of agricultural commodity to be planted is influenced by various factors whose process is very complex and dynamic. The purpose of this study is to analyze the relationship of characteristics to farmers' perception of the selection of horticultural crops in Bebesen District, Central Aceh Regency. The analysis model used is the Likert scale and Spearman rank by collecting primary and secondary data. The results of the study showed that the level of farmers' perception of horticultural commodity farming in Bebesen District, Central Aceh Regency was 66.3% and was classified as positive. Based on the results of the calculation of non-parametric statistical tests using the spearman rank test, this study shows that there isa relationship between farmer characteristics in the form of age, farming experience, and land area on farmer perception, but the latest education and the number of farmer family members have no influence on farmer perception in the selection of horticultural commodities in the research area.